Proposal of asymetric and weight transfer assessment and its relatin with hemiplegics functional activities (Fisioterapia e Pesquisa, 2001)
One of the most common locomotion deficit identified in hemiplegic people is the tendency to maintain asymmetrical posture, with a decreased weight bearing on the side involved and body weight shift towards the non-paretic side.